PROMISE (WA’AD) AND CONTRACT (’AQAD) ACCORDING TO ISLAMIC LAW: A COMPARATIVE STUDY - Mohamad, Muhammad Hisyam (Online Journal of Research in Islamic Studies, 2017)
It is reckoned that the key to competitiveness in any industry is research and innovation. Islamic finance industry – which is recognized as one of the fastest moving sector with an estimated annual average of 15% to 20% – has resorted to various approaches to cater for this pursuit. Wa‘ad which means a promise has turned out to be a vital tool, and it is gaining prominence as the industry players use it in conjunction with other Shariahcompliant products to achieve a desirable economic result. However, the application of wa‘ad together with an ‘aqad creates a polemic in the industry as the Muslim scholars are of different views with regards to the binding effect of wa‘ad. The majority of the classical views ruled that wa‘ad is not binding. However, the contemporary views inclined towards making wa‘ad as ‘aqad in terms of its bindingness. Thus, this article seeks to analyze this polemic by addressing the issue through a comparative study between a wa‘ad and an ‘aqad.